2023
DOI: 10.3390/gels9120986
|View full text |Cite
|
Sign up to set email alerts
|

Rheology in Product Development: An Insight into 3D Printing of Hydrogels and Aerogels

Raquel V. Barrulas,
Marta C. Corvo

Abstract: Rheological characterisation plays a crucial role in developing and optimising advanced materials in the form of hydrogels and aerogels, especially if 3D printing technologies are involved. Applications ranging from tissue engineering to environmental remediation require the fine-tuning of such properties. Nonetheless, their complex rheological behaviour presents unique challenges in additive manufacturing. This review outlines the vital rheological parameters that influence the printability of hydrogel and ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 212 publications
0
2
0
Order By: Relevance
“…In MEX processes, a filament extruder is replaced with a nozzle and fluid dispenser such as a syringe. This is a particularly advantageous process for all-cellulose feedstocks because it does not require melting; cellulosic materials exhibit shear thinning behavior, which improves printability during extrusion; and, the rheological properties of the feedstocks can be finely controlled by varying cellulose loadings and feedstock recipes [58,59]. Cellulose loading plays a critical role in feedstock printability because there is much greater shear thinning behavior for cellulose solutions with higher cellulose molecular weights (MW) and concentrations, whereas, in sufficiently dilute regimes, solution flow behavior is approximately Newtonian [60][61][62].…”
Section: Materials Extrusionmentioning
confidence: 99%
“…In MEX processes, a filament extruder is replaced with a nozzle and fluid dispenser such as a syringe. This is a particularly advantageous process for all-cellulose feedstocks because it does not require melting; cellulosic materials exhibit shear thinning behavior, which improves printability during extrusion; and, the rheological properties of the feedstocks can be finely controlled by varying cellulose loadings and feedstock recipes [58,59]. Cellulose loading plays a critical role in feedstock printability because there is much greater shear thinning behavior for cellulose solutions with higher cellulose molecular weights (MW) and concentrations, whereas, in sufficiently dilute regimes, solution flow behavior is approximately Newtonian [60][61][62].…”
Section: Materials Extrusionmentioning
confidence: 99%
“…In DIW processes, a filament extruder is replaced with a nozzle and fluid dispenser such as a syringe. This is a particularly advantageous process for all-cellulose inks because: it does not require melting; cellulosic materials exhibit shear thinning behavior, which improves printability during extrusion; and, the rheological properties of the inks can be finely controlled by varying cellulose loadings and ink recipes [62,63]. Cellulose loading plays a critical role in ink printability as it has been shown that there is much greater shear thinning behavior for cellulose solutions with higher cellulose molecular weights (MW) and concentrations, whereas, in sufficiently dilute regimes, solution flow behavior is approximately Newtonian [64][65][66].…”
Section: Direct Ink Writingmentioning
confidence: 99%